2010
DOI: 10.1088/0953-8984/22/11/115603
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of the layered Rh oxide K0.49RhO2

Abstract: We report measurements and analyses of resistivity, thermopower and Hall coefficient of singlecrystalline samples of the layered Rh oxide K 0.49 RhO 2 . The resistivity is proportional to the square of temperature up to 300 K, and the thermopower is proportional to temperature up to 140 K.The Hall coefficient increases linearly with temperature above 100 K, which is ascribed to the triangular network of Rh in this compound. The different transport properties between Na x CoO 2 and K 0.49 RhO 2 are discussed on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 54 publications
1
43
0
Order By: Relevance
“…A similar phenomenon was also observed in K 0.49 RhO 2 . 6 The T 2 relationship in the resistance (Fig. 3(b)) indicates that electronelectron interactions are the dominant scattering mechanism between 50 and 220 K. Temperature-dependent magnetization within the ab-and c-planes was also characterized, as shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A similar phenomenon was also observed in K 0.49 RhO 2 . 6 The T 2 relationship in the resistance (Fig. 3(b)) indicates that electronelectron interactions are the dominant scattering mechanism between 50 and 220 K. Temperature-dependent magnetization within the ab-and c-planes was also characterized, as shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…2 Another rhodium oxide, K 0.49 RhO 2 , also displays a large Seebeck coefficient (∼40 μV/K at 300 K), which is much greater than in many normal metals. 6 A giant thermoelectric effect was predicted in K 7/8 RhO 2 by the first principles calculations. 7 However, many important problems remain unresolved with regard to the K x RhO 2 system.…”
Section: Introductionmentioning
confidence: 91%
“…25 Although Rh is located just below Co in the periodic table, rhodium oxides have been less investigated than their cobalt-oxide counterparts, but recently have attracted considerable attention as candidates for thermoelectric oxides. [26][27][28][29][30][31][32][33] An advantage for the thermoelectric application is that the low-spin state is highly stable in Rh 3+ , which gives a large thermopower in the perovskite rhodium oxides. LaCoO 3 -based oxides show fairly good thermoelectric properties at room temperature, 34,35 but the thermopower suddenly decreases to a few μV/K above 500 K, accompanied by a spin-state crossover.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies confirmed that K x RhO 2 (x = 0.49 and 0.63) single crystals exhibits a moderate Seebeck coefficient at room temperature. 6,7 Upon doped with magnetic ions, K 0.58 RhO 2 showed a giant magnetoresistance and unconventional anomalous Hall effect below 10 K due to the formation of ferromagnetic clusters. 8 Though some studies have been conducted in this new material K x RhO 2 , there are still mysteries in this system.…”
mentioning
confidence: 99%